Empowerment on family caregivers for quality of life development in people living with HIV/AIDs - Choksawadphinyo, Kittiyaporn (Asia-Pacific Journal of Science and Technology, 2017)
This participatory action research utilized a 4 step empowerment processes conducted in three stages. Study participants, were 109 volunteers, comprising of 70 (64.2%) family caregivers and 39 (35.8%) HIV/AIDS (PLWHA) patients. The first stage study results suggested that family caregivers considered themselves to lack power in the areas of physical, psychological, spiritual, economic and social health. In the second stage, they were empowered through knowledge acquisition and cultivation of economic self- sufficiency in their daily lives. In addition, a campaign was conducted in this stage to establish community empathy for PLWHA. Third stage data suggests that family caregivers experienced an enhanced sense of empowerment with regard to knowledge, understanding, spiritual matters, support and unity. The outcomes associated with social associated with social support of family caregivers, representing the quality of life of PLWHA, were partitioned into objective and subjective indicators. Objective indicators included health and appropriate levels of self-care, while subjective indicators included higher self-esteem and an enhanced sense of acceptance from family and community. Associated with the adoption of the concept of economic self-sufficiency in their daily lives, PLWHA reported that they enjoyed enhanced satisfaction and were better able to accept the reality of their condition.